METAPHOR AND REGISTRATION FUNCTION: THE SPEAKER´S VISION OF THE WORLD AND ITS INTERFERENCE IN NATURAL LANGUAGE - Ferrarezi Jr, Celso (Linha D'Água, 2012)
This work aims to demonstrate how differentcommunities of Brazilian Portuguese speakers andindigenous languages of South America speakers registerhistorical and cultural aspects through nominations throughthe functional metaphorical construction. are presentedExamples are presented, showing that these names have agreater importance than its indexical function and warn tothe fact that the loss of these names entails the loss ofimportant historical and cultural knowledge, which canresult in loss of identity and values that are important to thecommunity of speakers.